2009
DOI: 10.1111/j.1529-8817.2009.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHETIC INORGANIC CARBON ACQUISITION IN AN ACID‐TOLERANT, FREE‐LIVING SPECIES OF COCCOMYXA (CHLOROPHYTA)1

Abstract: The processes of CO2 acquisition were characterized for the acid-tolerant, free-living chlorophyte alga, CPCC 508. rDNA data indicate an affiliation to the genus Coccomyxa, but distinct from other known members of the genus. The alga grows over a wide range of pH from 3.0 to 9.0. External carbonic anhydrase (CA) was detected in cells grown above pH 5, with the activity increasing marginally from pH 7 to 9, but most of the CA activity was internal. The capacity for HCO3 (-) uptake of cells treated with the CA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In this respect, based on the genetic analysis of Coccomyxa subellipsoidea strain, Blanc et al (2012) suggested the existence of a functional CO 2 -concentrating mechanism. Verma et al (2009) proposed the presence of an external carbonic anhydrase (CA) in Coccomyxa, which operates at pH above 7, with a carbon transport facilitating role rather than a concentrating function. These findings might also explain partly the moderate productivity values obtained for C. onubensis cultured at acidic pH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, based on the genetic analysis of Coccomyxa subellipsoidea strain, Blanc et al (2012) suggested the existence of a functional CO 2 -concentrating mechanism. Verma et al (2009) proposed the presence of an external carbonic anhydrase (CA) in Coccomyxa, which operates at pH above 7, with a carbon transport facilitating role rather than a concentrating function. These findings might also explain partly the moderate productivity values obtained for C. onubensis cultured at acidic pH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The physiology of both free-living and symbiotic Chlorella-like algae is affected by the acidic conditions of their respective habitats (McAuley, 1992;Dorling et al, 1997;Verma et al, 2009). However, less is known about what kind of physiological traits can evolve in algae involved in long-term intimate interactions with protist host organisms, specifically, in response to acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A free-living species of the trebouxophycean Coccomyxa had a CCM when grown at higher pH values than the lake water, in contrast to the symbiotic species of Coccomyxa examined previously which lacked a CCM. Verma et al (2009) independently reported that a freeliving strain of Cocomyxa expressed a CCM when grown at high pH. Diaz and Maberly (2009) noted that some of the algae they examined showed characteristics that could not readily be assigned to diffusive entry of CO 2 or the expression of a CCM.…”
Section: Introductionmentioning
confidence: 96%